FOTOTROPISMO EM PHASEOLUS VULGARIS: INFLUÊNCIA DA LUZ NO CRESCIMENTO CAULINAR - Hochmüller, Laura H. L.; Fronza, Camila; Possebon, Daniele B.; Ferreira, Lisiane D. O.; Gesing, João P. A. (Salão do Conhecimento, 2013)
Resumo